Post-extinction selective persistence of large dendritic spines in fear remodeled circuits may serve to reactivate fear. (December 2015) - Pignataro, Annabella; Ammassari-Teule, Martine
Highlights: Fear memory formation increases the number and the size of dendritic spines in fear-activated brain regions. Fear extinction resets the density but not the size of spines to baseline levels. Degradation of the extra cellular matrix into the basolateral amygdala prevents fear memory reactivation and disrupts post-extinction persistence of spine enlargement. Persistence of memory-driven large spines is needed to reactivate fear memory. Abstract : Memory formation associates with changes in strength and efficacy of existing synapses and with the formation of new synapses. Dendritic spines, the membranous protrusions from neuron dendrites that host the majority of excitatory synapses, are the anatomical sites where neuronal activity reshapes brain networks in response to stimuli. Mounting evidence indicates that structural changes in fear-remodeled circuits undergo partially erasure following extinction, suggesting that the changes that persist may serve to reactivate memory. Here we review data showing how brain circuits are remodeled at the time fear memory is formed and extinguished, with a special focus put on the post-extinction persistence of spine enlargement in relation to memory reactivation.